Activity Concentration of 226Ra and 232Th in Sediments and Seawater of Cirebon (Northern West Java) - Muhaemin, Moh; Wahyu Retno Prihatiningsih; Mohamad Nur Yahya; Yogi Priasetyono; Anggun Dinanti Pantis; Salsabela Marisya Athariq; Murdahayu Makmur; Deddy Irawan Permana Putra; Ambar Winansi (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 226Ra and 232Th were determined in sediments and seawater of Cirebon waters. The activity of natural radionuclides varies in Cirebon waters. Natural radioactivity in sediment is relatively higher than in seawater. Natural radioactivity in sediment and seawater is comparable to other regions' levels. Abstract 226Ra and 232Th are natural radionuclides with long half-lives, and they have a dangerous radiation exposure effect on marine biota and even humankind. This study investigates the activity concentration and horizontal distribution of natural radionuclides 226Ra and 232Th in sediments and seawater from the coastal waters of Cirebon, Indonesia, directly adjacent to the Cirebon Coal-Fired Power Station (CFPS). The activity concentrations of 226Ra and 232Th radioactivity were measured using gamma-ray spectrometry. Radioactivity analysis of 226Ra and 232Th was conducted on sediment and seawater columns. Furthermore, Ocean Data View (ODV) version 5.8.2 software was used to analyse the horizontal distribution pattern. The results showed that the highest concentrations of 226Ra and 232Th radioactivity were found in the sediment rather than the water column, even though they varied by location. The concentration activity of 226Ra and 232Th radioactivity was found to be a linear function of distance from the potential pollution source. Higher activity was detected at stations closer to the pollution source (CFPS). There was no significant effect of the depth of radionuclide distribution. Further monitoring activities at Cirebon’s CFPS should be conducted to predict and manage the impact on biota and human life.